2007
DOI: 10.1016/j.vaccine.2007.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunologic responses to multiple doses of IMVAMUNE® (Modified Vaccinia Ankara) followed by Dryvax® challenge

Abstract: Smallpox vaccination with replication deficient vaccinia strains such as Modified Vaccinia-Ankara (MVA) may induce protective immunity with improved safety and tolerability profiles compared with currently available smallpox vaccines. Ninety subjects were randomized equally to 6 groups in a partially blinded, randomized control clinical trial. IMVAMUNE ® (MVA-BN ® , Bavarian Nordic A/S, Kvistgård, Denmark) vaccine or placebo was administered at Study Day 0 and 28 by subcutaneous or intramuscular injection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
119
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 15 publications
13
119
0
4
Order By: Relevance
“…Our results showed that two-dose IMVAMUNE (6.26 ϫ 10 2 ) induced a higher peak level of NAbs (with day 0 at 30 days after the second vaccination) than Dryvax (2.38 ϫ 10 2 ) or Acambis2000 (8.94 ϫ 10 1 ). This is consistent with previous reports that "first-generation" vaccines induce similar higher levels of anti-VACV NAbs than "second-generation" vaccines (22), and it recapitulates findings (17) where, in human volunteers, two doses of MVA generated higher levels of NAbs than Dryvax alone. Similarly, in MPXV-infected NHP (13) and RPXV-infected rabbit challenge models (18), a twodose MVA regimen elicited higher levels of NAbs than Dryvax.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that two-dose IMVAMUNE (6.26 ϫ 10 2 ) induced a higher peak level of NAbs (with day 0 at 30 days after the second vaccination) than Dryvax (2.38 ϫ 10 2 ) or Acambis2000 (8.94 ϫ 10 1 ). This is consistent with previous reports that "first-generation" vaccines induce similar higher levels of anti-VACV NAbs than "second-generation" vaccines (22), and it recapitulates findings (17) where, in human volunteers, two doses of MVA generated higher levels of NAbs than Dryvax alone. Similarly, in MPXV-infected NHP (13) and RPXV-infected rabbit challenge models (18), a twodose MVA regimen elicited higher levels of NAbs than Dryvax.…”
Section: Discussionsupporting
confidence: 92%
“…2). Our results confirmed the boosting effect of the second dose of IMVAMUNE (17), as Abs induced with a single dose were 12.9-fold lower than the level induced by two doses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As a result of this pivotal study, poxvirus vectors are receiving renewed attention for delivery of tuberculosis (TB), malaria, and HIV antigens in various prime-boost combinations (5,8,9). Modified vaccinia virus Ankara (MVA) has been used as a candidate smallpox vaccine and has had a favorable safety profile in Ͼ100,000 humans (8,10,11). Multiple immunizations with MVA are tolerated, and both T-cell and antibody responses are detected in the majority of volunteers (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…This vaccine is currently stockpiled in the United States for use during an emergency, such as an imminent bioterrorist attack, to protect individuals who are at risk of developing side effects from older vaccines (37). Studies have been published demonstrating the safety, immunogenicity (4), and protective efficacy against vaccinia virus scarification in humans (38) of Imvamune delivered in a single-or twodose regime. Several studies have also shown its protective potency in animals (33,39,40).…”
Section: Discussionmentioning
confidence: 99%